Strategi Pembelajaran Pendidikan Agama Islam dalam Membentuk Perilaku Religius Siswa Autis - Riski Kristianto Pambudi; Joko Subando (Lembaga Yasin AlSys, 2026)
Islamic Religious Education (PAI) is oriented not only toward the transmission of knowledge about Islamic teachings, but also toward the formation of students’ personality and religious behavior. However, PAI learning for autistic students requires specific strategies because they have characteristics such as communication barriers, limited social interaction, and a tendency toward concrete and visual thinking. This study aims to examine PAI learning strategies in shaping the religious behavior of autistic students. This study used a qualitative approach with a library research method through a review of relevant literature on PAI learning strategies, the characteristics of autistic children, and the formation of religious behavior. The results of the review show that effective learning strategies for autistic students in PAI learning include an individual approach, the use of visual media, the provision of simple and gradual instructions, positive reinforcement, and the creation of a structured and consistent learning environment. These strategies need to be implemented based on learning principles that are structured, patterned, programmed, consistent, and continuous. These findings affirm that PAI teachers have a central role as educators, facilitators, motivators, and evaluators in supporting the formation of religious behavior among autistic students. The conclusion of the study shows that adaptive and consistent PAI learning strategies can help autistic students develop religious behavior in accordance with their abilities and learning characteristics. The implications of this study provide theoretical contributions to the development of inclusive PAI learning studies, as well as practical implications for teachers in designing learning that is more individual, visual, structured, and oriented toward the formation of individuals who are faithful, pious, and noble in character.